Heterozygous mutation in the SAM domain of p63 underlies Rapp-Hodgkin ectodermal dysplasia - Kantoputra P.N. (2014)
Several ectodermal dysplasia syndromes, including Ectrodactyly-Ectodermal dysplasia-Clefting (EEC) and Ankyloblepharon-Ectodermal Dysplasia-Clefting (AEC) syndromes, are known to result from mutations in the p63 gene. We investigated whether Rapp-Hodgkin syndrome (RHS) is also caused by mutations in the p63 gene. We identified a heterozygous de novo germline missense mutation, S545P, in the sterile-alpha-motif (SAM) domain of p63, in a Thai patient affected with RHS. This is the first genetic abnormality to be described in RHS. The amino acid substitution is the most downstream missense mutation in p63 reported thus far. Histological assessment of a skin biopsy from the patient's palm showed hyperkeratosis and keratinocyte cell-cell detachment in the upper layers of the epidermis, along with numerous apoptotic keratinocytes. Collectively, these investigations demonstrate that RHS is also caused by mutations in p63 and that the clinical similarities to AEC syndrome are paralleled by the nature of the inherent mutation.